Pengaruh Pelaksanaan Meditasi Sebelum Pembelajaran Untuk Meingkatkan Kemampuan Menangani Stres Akademik Siswa Agama Buddha - Panna Setiyawan; Endang Sri Rejeki; Sukisno Sukisno (Departement of Mathematics Education, 2023)
In an increasingly competitive and complex world, students, students, or anyone involved in education often faces various challenges that can trigger stress. Academic stress is a significant phenomenon, because it has a direct impact on a person's well-being and academic performance. The background of this research emphasizes the need for an understanding of the impact of meditation before learning on the ability to deal with academic stress of Buddhist students. The questionnaire distribution method was used in this study, and the data analysis technique used was correlational statistical techniques. The results of the analysis showed that there was an effect of meditation before learning in dealing with the academic stress of Buddhist students at SMP Negeri 1 Kaloran. However, a value of X = 0.633 + 0.400 Y (percentage value or coefficient number) shows how much influence the meditation has. Thus, meditation before learning has a role in dealing with simple linear regression problems between education and the ability to handle academic stress of Buddhist students.